Predictive Factors for Poor Outcomes Associated with COVID-19 in a Retrospective Cohort of Myasthenia Gravis Patients - Bi Z; Gao H; Lin J; Gui M; Li Y; Li Z; Bu B (Dove Medical Press, 2024)
Zhuajin Bi,1,2 Huajie Gao,1,2 Jing Lin,1,2 Mengcui Gui,1,2 Yue Li,1,2 Zhijun Li,1,2 Bitao Bu1,2 1Department of Neurology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei Province, People's Republic of China; 2Hubei Key Laboratory of Neural Injury and Functional Reconstruction, Huazhong University of Science and Technology, Wuhan, People's Republic of ChinaCorrespondence: Zhijun Li, Department of Neurology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei Province, People's Republic of China, Email lizhijun@tjh.tjmu.edu.cn Bitao Bu, Email bubitao@tjh.tjmu.edu.cnPurpose: To investigate the predictors for poor outcomes (including disease exacerbation, hospitalization and myasthenic crisis) in patients with pre-existing myasthenia gravis (MG) following Coronavirus disease 2019 (COVID-19), and to explore the potential effects of COVID-19 on inflammatory and immune responses in MG patients.Patients and Methods: This retrospective cohort study analyzed medical records of 845 MG patients who were diagnosed with COVID-19 between January 2020 to March 2023 at a single medical center.Results: Generalized MG at onset and comorbidities (chronic kidney disease and malignancy) were independent risk factors of poor outcomes. Patients achieving minimal manifestation or better status before COVID-19 had a significantly reduced risk for poor outcomes. Furthermore, patients with older onset age or anti-acetylcholine receptor antibody had a higher risk of exacerbation and hospitalization than those without. Prednisone or immunosuppressant treatment had the potential to reduce the occurrence of poor outcomes, while the duration of prednisone or immunosuppressant usage was associated with a higher risk of poor outcomes. Of the 376 MG patients with blood results available, patients with COVID-19 tended to have higher levels of leukocyte counts, neutrophil-lymphocyte-ratio, hypersensitive C-reactive protein, and Interleukin-6, as well as lower percentages of lymphocytes and regulatory T cells compared to patients without COVID-19.Conclusion: Disease severity at onset, comorbidities, and unsatisfactory control of myasthenic symptoms predicted the occurrence of poor outcomes in MG patients following COVID-19. The risk of poor outcomes was reduced in patients controlled by short-term immunosuppressive therapy. Novel coronavirus might affect inflammatory and immune responses in MG patients, particularly in altering interleukin-6 and regulatory T cell levels.Keywords: myasthenia gravis, COVID‐19, poor outcomes, immunosuppressive treatment, immune responses